ISOLATION AND CHARACTERIZATION OF POLYHYDROXYBUTYRATE-CO-VALERATE (PHBV) FROM MIXED CULTURES OF LOCAL STRAINS OF HALOPHILIC BACTERIA - Komariah, Siti
Plastic has become an important material in everyday life due to its lightness, strength, and cheapness. However, the use of petroleum-based plastics risks damaging the environment, especially due to their difficulty to decompose and microplastic pollution. The global dependence on plastics has triggered an increasingly urgent environmental crisis, requiring efforts to find more sustainable solutions. One of the efforts that can be made is to shift towards the use of alternative plastic replacement materials, namely bioplastics, which have the advantage of being biodegradable and derived from renewable resources. Polyhydroxyalkanoate (PHA) is a bioplastic produced by bacteria and has various applications, ranging from the packaging industry, medical field, to agriculture. PHA-derived bioplastics that have been widely researched to date are homopolymer PHA, Polyhydroxybutyrate (PHB) and copolymer PHA, Polyhydroxybutyrate-co-valerate (PHBV). The application of PHA is adjusted to the characteristics of each PHA, such as homopolymer PHA is used for materials that require more rigid properties, while copolymer PHA is used for materials that require more flexible or elastic properties. Previous research shows that there are local strains of halophilic bacteria that can produce PHB, namely Halomonas elongata BK-AG25 with a carbon source of glucose and Salinivibrio sp. with a carbon source in the form of palm oil mill effluent (POME). Research shows that the combination of several PHA-producing bacteria and a combination of carbon sources can produce PHA copolymers that can be used as an exploration of potential applications. The use of waste as a carbon source can support sustainable solutions. Therefore, this study aims to isolate PHA copolymer bioplastics from a mixed culture of halophilic bacteria local strain Halomonas elongata BK-AG25 and Salinivibrio sp. using POME as carbon source and determine the characteristics of the bioplastics. The products were characterized using Fourier Transform Infra-Red (FT-IR), Proton Nuclear Magnetic Resonance (1H-NMR), Gas Chromatography-Mass Spectrometry (GC-MS), Thermogravimetric Analysis/Differential Thermogravimetric (TGA/DTG), and Scanning Electron Microscope-Energy Dispersive System (SEM-EDS) methods, with the results then compared with data from the literature. The results showed that PHBV was successfully obtained as much as 56.3 ± 5.1 mg/L media. FT-IR spectrum showed absorption peaks at wavenumber 1234 ?????????1(C-O), 1380 ?????????1and 1455 ?????????1( CH3), 2928 ?????????1(-CH), 1730 ?????????1(C=O), and 3420 ?????????1(-OH). The 1H-NMR spectrum showed signals at chemical shift of 0.87 ppm (H on CH3 of hydroxyvalerate residue), 1.26 ppm (H on CH3 of hydroxybutyrate residue), 1.59 ppm (H on CH2 of hydroxyvalerate residue), 2.34 ppm and 5.34 ppm (H on CH2 and CH of hydroxybutyrate residue and hydroxyvalerate). The GC-MS spectrum also showed the suitability of PHBV fragmentation pattern marked by the appearance of m/z signals at 39, 41, 55, 69, and 83. The thermal characterization of the product using TGA/DTG showed a mass reduction of 33% and a decomposition temperature of 311? with a decomposition rate of 3.25% per minute. The morphology of the product forms aggregates with C and O atomic composition of 63.85% and 26.25% respectively as shown by SEM-EDS analysis. This research opens the opportunity to process POME waste into high economic value bioplastics as indicated by the potential application of PHBV in several industrial sectors.